2016
DOI: 10.1177/0954008316643766
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in thermal conductivity and mechanical properties via large-scale fabrication of boron nitride nanosheets

Abstract: In this study, a facial method of fabricating hexagonal boron nitride nanosheet (BNNS) was proposed. Isopropyl alcohol was employed as the solvent to obtain the BNNS via exfoliation of the pristine hexagonal boron nitride. The yield of the exfoliated BNNS with thickness less than 20 nm was as high as 0.17-0.2 mg mL À1 . The BN-and BNNS-filled polyamide 6 (PA6) composites were subsequently prepared by melt blending, and a comparison of thermal conductivity and mechanical properties of the resultant composites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…However, the mechanical strength, toughness, and elongation at break (%) values decreased with increasing BN content [ 31 ]. Polyamide 6 (PA6) and BN and exfoliated BN(BNNS) composites were produced by Li et al [ 32 ]. The tensile stress of PA6/BN composites was higher than neat PA6 but for BNNS composites, the greater enhancement was obtained due to the higher aspect ratio BNNS and interaction between the polymer and BNNS [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanical strength, toughness, and elongation at break (%) values decreased with increasing BN content [ 31 ]. Polyamide 6 (PA6) and BN and exfoliated BN(BNNS) composites were produced by Li et al [ 32 ]. The tensile stress of PA6/BN composites was higher than neat PA6 but for BNNS composites, the greater enhancement was obtained due to the higher aspect ratio BNNS and interaction between the polymer and BNNS [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide 6 (PA6) and BN and exfoliated BN(BNNS) composites were produced by Li et al [ 32 ]. The tensile stress of PA6/BN composites was higher than neat PA6 but for BNNS composites, the greater enhancement was obtained due to the higher aspect ratio BNNS and interaction between the polymer and BNNS [ 32 ]. The reinforcement effect of graphene-like BN on the gelatin was investigated by Biscarat et al [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the h‐BN has been widely used for the modification of polymer materials and especially for the preparation of thermally conductive but electrically insulating materials . Previous studies mainly focused on the exfoliation and the function of h‐BN to elevate TC of polymeric materials . For example, Gu et al reported a method to fabricate epoxy resin/boron nitride (EP/BN) composites through modifying BN.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-based thermally conductive composites have received much attention from scientists and researchers due to their low weight, electrical insulation, corrosion resistance, and most importantly, their easy processing. 4,5 Therefore, thermally conductive polymer-based composites are often designed for applications in many fields, such as in light-emitting diodes (LEDs), electronic packaging, thermal interface materials, and integrated circuits. 6,7 Unfortunately, polymers have very low thermal conductivity (generally less than 0.4 W/m·K), 8,9 which is far below the requirements for effective heat dissipation in devices.…”
Section: Introductionmentioning
confidence: 99%